Unemployed college graduates' perception of the existing unemployment condition in the country - Arroz, Mizpah B .; Duarte, Iris Faye M. . (2005.)
The study seeks to know how the unemployed college graduates perceived the existing unemployment condition in the country. forty-five (45) unemployed college graduates in the town of Miag-ao served as respondents of the study. Majority of them were between 20-25 years of age., Interview schedule was used in the gathering data. Data were analyzed using frequency counts and percentages. Results show that generally, unemployed college graduates of Miag-ao have a positive perception that they can find job. Work experiences, high educational attainment and personal connections were the reasons of respondents that they will be employed in the future. However steep competition and rigid requirements set by agencies and companies turned to be the reasons for unemployment. With regard to job preferences, most of the respondents wanted to work in government agencies because it offers more benefits compared to private agencies. It further reveals that working abroad is the best resort for employment. Majority has plans of finding job outside the country for it offers higher salary and more job opportunities than in the country. The researchers recommend that further study be conducted regarding college graduates' perception of the unemployment condition in the country. The Local Government or nOn-Government Organizations also in the community could initiate programs or activities that would give these individuals income while they are still unemployed.
Thesis (Undergraduate, Bachelor of Arts in Community Development) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Unemployment. -- Philippines